FORMATION OF COGNITIVE COMPONENT OF PREPAREDNESS OF FUTURE INFORMATICS TEACHERS FOR MONITORING EDUCATIONAL ACHIEVEMENTS OF PUPILS IN PROFILE SCHOOL - Mazur, Natalia P. (Educological discourse, 2014)
In this article three components and degrees of the preparedness of future informatics teachers for monitoring students’ educational achievements are mentioned. Besides, it was characterized the organization and pedagogical conditions of effective formation the given preparedness. It was described the content of the experimental research of formation of the cognitive component of the preparedness for realizing the monitoring activity by future informatics teachers in the profile school and the received results were introduced. In the final part it was indicated the directions which require further research.